Non-targeted Effects of lonizing Radiation in Fish Cell Lines - O'Neill, Alicia (My University, 2006)
This study is one of the first to examine non-targeted effects of radiation in fish cell lines, with the aim of identifying a reliable reporter system for evaluating radiation damage in fish. The ability of the fish cell lines to clone was determined as the clonogenic assay was a major end point used to measure survival. A direct survival curve was completed for all cell lines that were deemed clonogenic using a cobalt-60 γ-radiation source. Non-targeted effects of radiation were evaluated by conducting bystander experiments on all fish cell lines. Delayed Cell Death (DCD) experiments were completed on the fish cell line that showed evidence of a cell death associated bystander effect as these phenomena may be linked. Four of the eight cell lines were found to be clonogenic. The cell line, RTG-2, was found to be the most radiosensitive at lower doses. All of the clonogenic cell lines, with the exception ofRTG-2 cells, generally showed increased Plating Efficiency (P.E.) when Irradiated Cell Conditioned Media (ICCM) was tested on unirradiated autologous cells. ICCM from the clonogenic and non-clonogenic cells was also tested on the mammalian cell line. This resulted in increased cell survival, with the exception of the RTS-pBk+ (p<O.OOl), RTS-34st (p<O.Ol) and ZEB 2J (p<0.05) cell lines. Since RTG-2 showed the most prominent cell killing bystander effect, DCD experiments were performed on this cell line. DCD was found in the progeny of irradiated parental cells at all doses tested. Cell kinetics also showed the generation of possible DCD. The results show that both bystander signal production and cellular responses vary depending on the cell line and that DCD and bystander effects are tentatively linked through genomic instability. The RTG-2 cell line may be a suitable model for a reliable reporter system to aid in determining the nontargeted effects of radiation in fish in the environment.
Keywords: Ionizing Radiation; Fish Cell; radiation; fish